Methodological application to studies of ecological-economic zoning in coastal areas. Chimbote case - Cabrera Carranza, Carlos Francisco (2000)
The city of Chimbote presents fishing as one of its main activities, which makes it consider one of the ports with the highest fishing production in Peru. Other activities are the steel industry, among others. These productive activities are leading this city to a deterioration of the environment, one of its causes being the application of inadequate technologies and the misuse of space. Ecological-economic zoning is considered as a planning instrument, which aims to promote the harmonious development of a territory. The present work proposes a methodology, which approximates the proposal of hierarchization of environmental variables, modified according to Etter, (1990) and consists of evaluating a certain situation, from studies of landscapes, plant associations, pedological studies and climatic, all of static type, without considering the evolution and the flows that define the structures.